2005
DOI: 10.1002/path.1894
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene expression profile distinguishes CD4+/CD57+ T cells of the nodular lymphocyte predominance type of Hodgkin's lymphoma from their tonsillar counterparts

Abstract: Little is known about the cytokine profile of nodular lymphocyte predominance Hodgkin's lymphoma (NLPHL) and the significance of the characteristic rosetting CD4(+)/CD57(+) T cells. We analysed the T lymphocyte populations isolated from lymph node suspensions from five patients with NLPHL, two with follicular hyperplasia and progressive transformation of germinal centres (PTGC), three with classical Hodgkin's lymphoma (CHL) and five with hyperplasia of the tonsil. We sorted the T cells based on expression of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 30 publications
2
26
0
1
Order By: Relevance
“…29 However, we have recently reported that in contrast to their tonsillar counterparts, CD4 + /CD57 + T-cells of NLPHL do not express IL4 even after PMA-ionomycine activation. 2 This suggests that in NLPHL, c-Maf and MUM1/ IRF4 induced expression of IL4 is blocked. c-Maf also has a transforming ability, 30 and has been shown to function as an oncogene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 However, we have recently reported that in contrast to their tonsillar counterparts, CD4 + /CD57 + T-cells of NLPHL do not express IL4 even after PMA-ionomycine activation. 2 This suggests that in NLPHL, c-Maf and MUM1/ IRF4 induced expression of IL4 is blocked. c-Maf also has a transforming ability, 30 and has been shown to function as an oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…2 HL associated T H cells may represent an influx of T H cells from the circulation into the lymphoid tissues. In both types of HL, the T-cells rosetting around the neoplastic cells have a helper/inducer memory phenotype (CD4 + /CD45RO + ), express CD28 and display an activated phenotype with expression of CD69.…”
mentioning
confidence: 99%
“…[2][3][4][5] In return, these infiltrating cells produce cytokines that may contribute to proliferation and survival of the HRS cells. 6,7 The CD4 þ T cells surrounding the neoplastic cells in both cHL and NLPHL are CD45RO þ /CD45RAÀ/CD45RB dim , suggesting a memory Th2 phenotype. 8 Expression of several activation-associated surface markers, including CD38, CD69 and HLA class II, indicates that these CD4 þ T cells are activated.…”
mentioning
confidence: 99%
“…4A). These atypical T cells were identified as CD3 low CD4 + CD7 À CD10 + CD26 À CD57 + (data not shown), a phenotype characteristic of leukemic cells in CTCL [23,24]. They did not show a Treg phenotype (FoxP3 À CD25 low , data not shown).…”
Section: Expansion Of Malignant T Cells In Patientmentioning
confidence: 82%